Is public broadcasting too expensive? An evaluation of the EBC budget - Pieranti, Octavio [UNESP] (Univ Federal Sergipe, 2020)
EBC's alleged high cost has been used as one of the arguments supporting the option to privatize the company. This article aims to assess whether this cost is really high based on EBC's historical budget and on a comparison of these values with that of foreign public broadcasters. This analysis shows that, according to the adopted criteria, EBC's cost is low, and it is important to highlight the decrease in the percentage of the budget allocated to investments in recent years. The company has been limited to the payment of its employees and regular operating expenses.
Keywords: EBC; Budget; Privatization